MAIN DIRECTIONS OF DEVELOPMENT OF SMALL PRODUCTION ENTERPRISES IN NAMANGAN REGION (Conference Zone, 2022)
In the article, consider the problems of small manufacturing business in Namangan region, their solutions and the main directions of development in the future.